Spectroscopic studies and molecular modeling for understanding the interactions between cholesterol and cyclodextrins - Delphine Castagne; Georges Dive; Brigitte Evrard; Michel Frédérich; Géraldine Piel (Frontiers Media S.A., 2010)
PURPOSE: Cholesterol is a major lipid constituent of biological membranes which could be included in cyclodextrin (CD) cavities. Solubilization and cell extraction of cholesterol have been previously performed in order to study its interaction with beta-CD and methylated beta-derivatives notably. The present work aims at confirming the formation of inclusion complexes between these CDs and cholesterol in order to understand their solubilization and cell extraction capacities. METHODS: In this context, liquid-state NMR spectroscopy (1H NMR studies and ROESY experiments) as well as theoretical studies (molecular modeling) have been performed. RESULTS: Rather than preferential conformations, the spectroscopic studies showed us the possible interactions between cholesterol and dimethyl-beta-CD, trimethyl-beta-CD, randomly methylated beta-CD or Crysmeb®. Weak interactions were detected using the latter one, confirming the advantage of the low substitution to decrease membrane loss of integrity and cytotoxicity. Molecular modeling studies should be used to determine which stoichiometry and conformations are energically more favorable. The semi-empirical AM1 level was used to investigate both 1:1 and 1:2 complexes whereas 1:1 complexes were also studied using minimal or double zeta basis sets. Four conformations for each 1:2 complexes have been envisaged and studied for the methylated CDs. CONCLUSIONS: These studies allowed us to confirm the interactions between cholesterol and beta-CDs especially the methylated derivatives.